Efektivitas animal assisted therapy (AAT) ikan cupang dalam meningkatkan kualitas tidur pada anak yang menjalani hospitalisasi - Atik Aryani; Widiyono Widiyono; Dhian Riskiana Putri (Holistik Jurnal Kesehatan, 2023)
Background: Hospitalization is a condition where a child must undergo treatment in hospital to restore health. The impact of hospitalization causes children to feel anxious, afraid of various invasive actions, children feel uncomfortable, decreased appetite, and decreased sleep quality. The hospital environment and health service delivery activities cause sleep problems in children who are undergoing treatment so that they can affect sleep quality. Decreased sleep quality can hinder the healing process and affect a child's growth and development. Treatment of sleep disorders can be done in two ways, namely pharmacological and non-pharmacological. Pharmacologically, sedative drugs can be given, but giving drugs can risk disrupting growth and development if given to children. Therefore, non-pharmacological management is a safe alternative. One of the non-pharmacological therapies that can be provided is through Animal Assisted Therapy (ATT) for Betta Fish.Purpose: To analyze the effectiveness of Animal Assisted Therapy (ATT) betta fish as a nursing intervention in improving sleep quality in children undergoing hospitalization.Method: This research design uses one group pre-test post-test group. The sampling technique used purposive sampling with a total sample of 30 respondents. Data collection used the Standard Operational Procedures for betta fish Animal Assisted Therapy (AAT) interventions and the Children's Sleep Habit Questionnaire (CSHQ) instrument to measure sleep quality. Data analysis used the Paired t-test statistical test.Results: The average quality of sleep before the intervention was given was 43,53 and the average quality of sleep after the intervention was 36,23. The results of the paired t-test obtained a p value of 0.001 (<0.05), which means that betta fish's animal assisted therapy (AAT) is effective in improving sleep quality in children undergoing hospitalization.Conclusion: Giving betta fish with Animal Assisted Therapy (AAT) as a complementary therapy can help improve sleep quality in children undergoing hospitalization.Suggestion: It is hoped that this intervention can be used as a non-pharmacological therapeutic method in treating sleep problems in children.Keywords: Animal Assisted Therapy (AAT); Betta Fish; Children; Hospitalization; Sleep QualityPendahuluan: Hospitalisasi merupakan kondisi dimana anak harus menjalani perawatan di rumah sakit untuk pemulihan kesehatan. Dampak hospitalisasi menyebabkan anak merasa cemas, takut dengan berbagai tindakan invansif, anak merasa tidak nyaman, nafsu makan menurun, dan kualitas tidur menurun.Lingkungan rumah sakit dan aktivitas pemberian pelayanan kesehatan menyebabkan masalah tidur pada anak yang sedang menjalani perawatan sehingga dapat memengaruhi kualitas tidur. Kualitas tidur yang menurun dapat menghambat proses penyembuhan dan memengaruhi tumbuh kembang anak. Penanganan gangguan tidur dapat dilakukan melalui dua cara yaitu farmakologi dan nonfarmakologi. Secara farmakologi dapat diberikan obat-obatan sedative, namun pemberian obat dapat beresiko menganggu tumbuh kembang jika diberikan pada anak.Oleh karena itu penatalaksanaan nonfarmakologi menjadi alternatif yang aman dilakukan.Salah satu terapi nonfarmakologis yang dapat diberikan melalui Animal Assisted Therapy (ATT) Ikan Cupang.Tujuan: Untuk menganalisis efektivitas Animal Assisted Therapy (ATT) ikan cupang sebagai intervensi keperawatan dalam meningkatkan kualitas tidur pada anak yang menjalani hospitalisasi.Metode: Desain penelitian ini menggunakan one group pre-test post-test group. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel sebanyak 30 responden. Pengumpulan data menggunakan Standar Operasional Prosedur intervensi Animal Assisted Therapy (AAT) ikan cupang dan instrumen Children’s Sleep Habit Questionnaire (CSHQ) untuk mengukur kualitas tidur. Analisis data menggunakan uji statistik Paired t-test.Hasil: Menunjukkan rerata kualitas tidur sebelum diberikan intervensi sebesar 43,53 dan rerata kualitas tidur setelah diberikan intervensi sebesar 36,23. Hasil uji paired t-test didapatkan nilai p value sebesar 0,001 (<0,05) yang berarti animal assisted therapy (AAT) ikan cupang efektif dalam meningkatkan kualitas tidur pada anak yang menjalani hospitalisasi.Simpulan: Pemberian Animal Assisted Therapy (AAT) ikan cupang sebagai terapi komplementer dapat membantu dalam peningkatkan kualitas tidur pada anak yang menjalani hospitalisasi.Saran: Intervensi ini diharapkan dapat dimanfaatkan sebagai metode terapi non farmakalogi dalam mengatasi masalah tidur pada anak.